Peran Online Customer Experience Dalam Meningkatkan Customer Satisfaction Dan Repurchase Intention Pada Platform Digital - Saputra, Galih Ginanjar; Fadhilah, Fadhilah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
In the rapidly evolving digital era, digital platforms have become an integral part of consumers' daily lives. Digital platforms include various types of services, ranging from e-commerce, social media, digital banking apps, to entertainment platforms such as video streaming. Shopee is a digital platform in the form of e-commerce with the largest number of users in Indonesia. This study aims to investigate the role of Online Customer Experience in increasing Customer Satisfaction and Repurchase Intention on the Shopee digital platform. The type of research used is explanatory research with a quantitative approach, where the data collected is in the form of numbers and analyzed using statistics. The data analysis method used in this study is Path Analysis. The variables studied include the independent variable Online Customer Experience (X), the intervening variable Customer Satisfaction (Y), and the dependent variable Repurchase Intention (Z). This study involved 136 respondents who were users of the Shopee platform. The results of the study show that Customer Experience has a significant influence on Customer Satisfaction and Repurchase Intention on the Shopee digital platform. This research can also provide valuable insights for business practitioners and digital platform owners in developing better customer experience strategies to face the increasingly fierce competition in the digital world.